A Au and Co co-doped holmium ferrite gas-sensitive material and its application

By co-doping holmium ferrite gas-sensitive materials with Au and Co, the problem of high-temperature operation of holmium ferrite gas-sensitive materials has been solved, achieving low-temperature high-efficiency formaldehyde detection and improved stability, making it suitable for various application scenarios.

CN119143186BActive Publication Date: 2025-01-10SHANDONG JIANZHU UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411657625.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-01-10
Estimated Expiration
2044-11-20

AI Technical Summary

Technical Problem

When existing holmium ferrite gas-sensitive materials are used for formaldehyde detection, the operating temperature is as high as 315℃, which causes the material to sinter or oxidize, reducing sensitivity and increasing energy consumption, making it difficult to meet the needs of various application scenarios.

Method used

Holmium ferrite gas-sensitive materials co-doped with Au and Co are prepared by the sol-gel method. By combining the catalytic activation of the noble metal Au and the oxygen vacancy regulation of Co, the operating temperature is reduced to 80-200℃, thereby improving the material's response sensitivity and selectivity to formaldehyde.

Benefits of technology

Achieving rapid formaldehyde detection at lower temperatures significantly reduces energy consumption and improves material stability and selectivity, making it suitable for portable or low-power devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119143186B_ABST
    Figure CN119143186B_ABST
Patent Text Reader

Abstract

The invention discloses a Au and Co co-doped holmium ferrite gas-sensitive material and its application, and relates to the technical field of formaldehyde gas sensors. The invention adopts holmium nitrate, ferric nitrate and cobalt nitrate as reaction raw materials, and obtains Co-doped holmium ferrite material by sol-gel method, and then mixes it with chloroauric acid and calcines it to obtain Au and Co co-doped holmium ferrite gas-sensitive material. The invention utilizes the catalytic activation of Au and the oxygen vacancy regulation effect of Co, and the surface of the material can more stably adsorb and decompose formaldehyde molecules, showing better selectivity compared with non-polar interfering gases. At the same time, by utilizing the synergistic effect of the molecular characteristics of formaldehyde and the doping of Au and Co, not only the response sensitivity and selectivity of the material to formaldehyde are improved, but also the rapid low-temperature detection of formaldehyde gas is realized, and the energy consumption of the gas-sensitive material is significantly reduced, so that it has good stability and long-term performance in practical applications.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of formaldehyde gas sensors, and in particular to an Au and Co co-doped holmium ferrite gas-sensitive material and application thereof. Background Art

[0002] Formaldehyde (HCHO), also known as formic acid, is a toxic substance with high solubility and volatility. Its main health hazards to the human body are: irritation to the skin and mucous membranes, impact on the central nervous system, induction of genetic diseases and tumors. The World Health Organization's International Agency for Research on Cancer has identified formaldehyde as a carcinogen and teratogen. It can be seen that effective monitoring of formaldehyde concentration in the environment is particularly important for human health. A gas sensor is a device that converts information about the concentration of a specific gas into an electrical signal and detects changes in the concentration of a specific gas based on the electrical signal. It is favored because of its advantages such as simple operation, easy portability, and fast and effective online monitoring.

[0003] In the prior art, the paper "Study on the Effect of Lanthanum Ferrite Modification on Formaldehyde Gas Sensitivity" (Lin Yutao, Yunnan University, May 2012) discloses the use of sol-gel method combined with microwave chemical method to prepare Ag-modified LaFeO3 gas-sensitive materials, the optimal working temperature of which is 90°C, at which the highest sensitivity to 1ppm formaldehyde can reach about 20. Studies have shown that compared with single oxides, composite oxide gas-sensitive materials often have better selectivity and thermal stability. The journal "Preparation of Holmium Ferrite and Samarium Ferrite Nanocrystals and Study on Their Formaldehyde Sensitivity Characteristics" (Jiang Dongli et al., New Chemical Materials, Vol. 45, No. 10, October 2007) discloses the use of solid-phase reaction method to prepare perovskite composite oxide holmium ferrite at a working temperature of 315°C, which has a high sensitivity to formaldehyde, and its sensitivity to formaldehyde gas is 20.4. It can be seen that when holmium ferrite alone is used as a gas-sensitive material for formaldehyde gas detection, its operating temperature is as high as 315°C. It can be seen that when the unmodified composite oxide material - holmium ferrite is selected as the formaldehyde gas-sensitive material, its operating temperature is as high as 315°C. Excessively high temperature may cause sintering or oxidation of the gas-sensitive material, thereby reducing sensitivity and increasing the energy consumption of the sensor.

[0004] Therefore, it is particularly important to develop a formaldehyde sensor based on new gas-sensitive materials, while ensuring its sensitivity and selectivity for detecting formaldehyde gas, lowering the operating temperature to enhance the long-term stability of the formaldehyde sensor, so as to better adapt to the needs of various application scenarios. Summary of the invention

[0005] In view of the above-mentioned prior art, the purpose of the present invention is to provide Au and Co co-doped holmium ferrite gas-sensitive materials and their applications. The present invention adopts holmium nitrate, iron nitrate and cobalt nitrate as reaction raw materials, and obtains Co-doped holmium ferrite materials by sol-gel method, and then mixes the Co-doped holmium ferrite materials with chloroauric acid, grinds and calcines, and obtains Au and Co co-doped holmium ferrite gas-sensitive materials. The present invention performs Au and Co doping modification on the composite oxide holmium ferrite, and utilizes the catalytic activation of Au and the oxygen vacancy regulation effect of Co, so that the surface of the material can more stably adsorb and decompose formaldehyde molecules, and exhibits better selectivity compared with non-polar interfering gases. At the same time, the molecular characteristics of formaldehyde and the synergistic effect of Au and Co doping are utilized, which not only improves the response sensitivity and selectivity of the material to formaldehyde, but also realizes the rapid low-temperature detection of formaldehyde gas, significantly reduces the energy consumption of the gas-sensitive material, and makes it have good stability and long-term effect in practical applications.

[0006] To achieve the above object, the present invention adopts the following technical solution:

[0007] In a first aspect of the present invention, there is provided an Au and Co co-doped holmium ferrite gas-sensitive material, wherein the Au and Co co-doped holmium ferrite gas-sensitive material is prepared by the following method:

[0008] (1) mixing holmium nitrate, ferric nitrate, cobalt nitrate and citric acid to obtain a mixture, then adding the mixture into dilute nitric acid and stirring to mix well to obtain a precursor solution;

[0009] (2) heating the precursor solution in a water bath at 50-85°C and cooling it to obtain a solid; calcining the solid at 650-1050°C for 3-12h and then grinding it to obtain a Co-doped holmium ferrite material;

[0010] (3) After mixing the Co-doped holmium ferrite material and chloroauric acid, the mixture is ground once, calcined at 650-1050°C for 3-12h, and then ground twice to obtain the Au and Co co-doped holmium ferrite gas sensing material;

[0011] The added amount ratio of holmium nitrate, ferric nitrate, cobalt nitrate, chloroauric acid, citric acid and dilute nitric acid is (0.01-5) mol: (0.05-5) mol: (0.01-5) mol: (0.01-100) g: (20-100) g: (50-200) mL.

[0012] Preferably, in step (1), the mass fraction of dilute nitric acid is 8-9%.

[0013] Preferably, in step (1), the stirring time is 6-12 hours.

[0014] Preferably, in step (2), during the water bath heating process, the precursor solution is stirred at a stirring speed of 500-600 r / min and a stirring time of 2-8 h.

[0015] Preferably, in step (2), the grinding time is 2-6 hours.

[0016] Preferably, in step (3), the time for the first grinding and the second grinding is 2-6 hours.

[0017] The second aspect of the present invention provides the use of the Au and Co co-doped holmium ferrite gas-sensitive material in formaldehyde gas detection.

[0018] Preferably, the concentration of the formaldehyde gas is 0.5-1.5 ppm.

[0019] The third aspect of the present invention provides the use of the Au and Co co-doped holmium ferrite gas-sensitive material in the preparation of a formaldehyde gas sensor.

[0020] Preferably, the formaldehyde gas sensor is prepared by the following method: Au and Co co-doped holmium ferrite gas-sensitive material, deionized water and pinene alcohol are mixed to obtain a mixture, the mixture is spin-coated on a substrate to form a gas-sensitive film, and the gas-sensitive film is aged to obtain a formaldehyde gas sensor.

[0021] Further preferably, the added amount ratio of Au and Co co-doped holmium ferrite gas-sensitive material, deionized water and pinene alcohol is (1-5) g: (3-15) mL: (1-5) mL.

[0022] More preferably, the aging temperature is 200-240° C., and the aging time is 10-24 h.

[0023] Preferably, the operating temperature of the formaldehyde gas sensor is 80-200°C.

[0024] Beneficial effects of the present invention:

[0025] The present invention uses holmium nitrate, ferric nitrate, and cobalt nitrate as reaction raw materials, and obtains Co-doped holmium ferrite material through a sol-gel method. The Co-doped holmium ferrite material is then mixed with chloroauric acid, and then ground and calcined to obtain Au and Co co-doped holmium ferrite gas-sensitive material. The present invention performs doping modification of the composite oxide holmium ferrite with Au elements and Co elements. While ensuring its sensitivity and selectivity for detecting formaldehyde gas, it is particularly important to reduce the operating temperature to enhance the long-term stability of the formaldehyde sensor to better adapt to the needs of various application scenarios. Specifically, the Au and Co co-doped holmium ferrite gas-sensitive material obtained by the present invention has good selectivity for formaldehyde gas, and its optimal operating temperature is 140°C. At this operating temperature, its response to 1ppm formaldehyde gas is 5.96. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 : XRD pattern of Au and Co co-doped holmium ferrite gas-sensitive material prepared in Example 1;

[0027] Figure 2 : SEM image of Au and Co co-doped holmium ferrite gas-sensitive material prepared in Example 1;

[0028] Figure 3 : EDS Mapping diagram of gold and cobalt elements of the Au and Co co-doped holmium ferrite gas-sensitive material prepared in Example 1;

[0029] Figure 4 : A graph showing the relationship between the gas-sensing performance of the gas-sensitive materials prepared in Example 1 and Comparative Examples 1-3 to 1 ppm of formaldehyde gas and temperature;

[0030] Figure 5 : A graph showing the relationship between the gas-sensing performance of the Au and Co co-doped holmium ferrite gas-sensitive material prepared in Example 1 to 1 ppm formaldehyde gas and humidity;

[0031] Figure 6 : Schematic diagram of the response of the Au and Co co-doped holmium ferrite gas-sensitive material prepared in Example 1 to various gases at 1 ppm;

[0032] Figure 7 : Schematic diagram of the long-term gas-sensitive stability of the Au and Co co-doped holmium ferrite gas-sensitive material prepared in Example 1 to formaldehyde gas. DETAILED DESCRIPTION

[0033] It should be noted that the following detailed descriptions are illustrative and are intended to provide further explanation of the present application. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present application belongs.

[0034] In the prior art, compared with single oxides, composite oxide gas-sensitive materials often have better selectivity and thermal stability. Although the holmium ferrite material prepared by the solid-phase reaction method has a high sensitivity to formaldehyde, its operating temperature is 315°C. Such a high operating temperature will cause the holmium ferrite material to sinter or oxidize, thereby reducing its sensitivity and increasing the energy consumption of the gas sensor.

[0035] Based on this, the present invention provides a Au and Co co-doped holmium ferrite gas-sensitive material. The present invention performs Au and Co doping modification on the composite oxide holmium ferrite. While ensuring its sensitivity and selectivity for detecting formaldehyde gas, it is particularly important to reduce the operating temperature to enhance the long-term stability of the formaldehyde sensor to better meet the needs of various application scenarios. Specifically, the Au and Co co-doped holmium ferrite gas-sensitive material prepared by the present invention has good selectivity for formaldehyde gas, and its optimal operating temperature is 140°C. At this operating temperature, its response to 1ppm formaldehyde gas is 5.96.

[0036] The present invention utilizes the sol-gel method, utilizes the noble metal Au to load and modify the HoFeO3 surface, and simultaneously dopes the Co element at the B position. Through the composite doping design of the noble metal and the B position, the prepared formaldehyde gas-sensitive material exhibits excellent sensitivity in detecting HCHO gas, and can effectively distinguish HCHO gas from other interfering gases. At the same time, the prepared formaldehyde gas-sensitive material can reduce the operating temperature of the sensor to 80-200° C., reduces the energy consumption of the sensor, and is suitable for portable or low-power consumption devices.

[0037] Formaldehyde (HCHO) is a small molecule, highly polar and chemically active gas. Its carbonyl group (C=O) has significant electron attraction characteristics and is easy to react with active sites on the surface of gas-sensitive materials. The present invention modifies holmium ferrite by co-doping Au and Co, and utilizes these molecular characteristics of formaldehyde to produce a synergistic effect with the doping elements, thereby significantly improving the gas-sensitive performance of the material to formaldehyde.

[0038] First, Au, as a noble metal, plays a significant catalytic sensitization role on the surface of the material. The carbonyl group of the formaldehyde molecule is easily adsorbed and activated by the Au surface to form reactive oxygen species (such as O - ), which accelerates the oxidation reaction of formaldehyde molecules on the surface of the material. At the same time, due to the catalytic effect of Au, the activation energy of formaldehyde is greatly reduced, allowing the material to efficiently detect formaldehyde at a lower temperature. This rapid oxidation reaction causes a significant change in the material's resistance, which effectively improves the sensitivity and speed of the gas-sensitive response, allowing the material to sensitively respond to formaldehyde at low temperatures of 100-200°C.

[0039] In addition, Co doping introduces a large number of oxygen vacancies into the material, further improving the gas sensing performance. Formaldehyde molecules are oxygen-philic and easily combine with these oxygen vacancies to form adsorbed formic acid (HCOO -) and other substances, thereby accelerating the decomposition and conversion process of formaldehyde. Oxygen vacancies not only provide sufficient active sites for the oxidation reaction of formaldehyde, but also optimize the conductivity of the material, making the oxidation reaction of formaldehyde more efficient. This oxygen vacancy effect significantly enhances the adsorption and reaction rate of formaldehyde, further improving the low-temperature response performance of the material.

[0040] Through the catalytic activation of Au and the oxygen vacancy regulation effect of Co, the surface of the material can more stably adsorb and decompose formaldehyde molecules, showing better selectivity compared with non-polar interfering gases (such as methane, ethane, etc.). The synergistic effect of the molecular characteristics of formaldehyde and the doping of Au and Co not only improves the response sensitivity and selectivity of the material to formaldehyde, but also realizes rapid low-temperature detection of formaldehyde gas, significantly reduces the energy consumption of gas-sensitive materials, and makes it have good stability and long-term effectiveness in practical applications.

[0041] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in conjunction with specific embodiments.

[0042] The experimental materials used in the embodiments of the present invention are all conventional experimental materials in the art and can be purchased through commercial channels.

[0043] Example 1: Preparation of Au and Co co-doped holmium ferrite gas-sensitive material

[0044] (1) Mix holmium nitrate, ferric nitrate, cobalt nitrate and citric acid to obtain a mixture, then add the mixture into 8.5% by mass dilute nitric acid, stir for 8 hours to mix, and obtain a precursor solution;

[0045] (2) The precursor solution was placed in a water bath at 80°C for heating, and stirred at a speed of 500 r / min for 6 hours during the water bath heating process, and cooled to room temperature to obtain a solid; the solid was calcined at 900°C for 8 hours and then ground for 3 hours to obtain a Co-doped holmium ferrite material;

[0046] (3) After mixing the Co-doped holmium ferrite material and chloroauric acid, the mixture was ground for 3 h, calcined at 900 °C for 8 h, and then ground for another 3 h to obtain the Au and Co co-doped holmium ferrite gas sensing material;

[0047] Among them, the added amount ratio of holmium nitrate, ferric nitrate, cobalt nitrate, chloroauric acid, citric acid and dilute nitric acid is 39.29g:19.35g:3.65g:2.29g:60g:50mL.

[0048] Example 2: Preparation of Au and Co co-doped holmium ferrite gas-sensitive material

[0049] (1) Mix holmium nitrate, ferric nitrate, cobalt nitrate and citric acid to obtain a mixture, then add the mixture into 8% by mass dilute nitric acid, stir for 8 hours to mix, and obtain a precursor solution;

[0050] (2) The precursor solution was placed in a water bath at 50°C and stirred at a speed of 600 r / min for 8 hours during the water bath heating process, and then cooled to room temperature to obtain a solid; the solid was calcined at 650°C for 10 hours and then ground for 2 hours to obtain a Co-doped holmium ferrite material;

[0051] (3) After mixing the Co-doped holmium ferrite material and chloroauric acid, grind for 2 hours, calcine at 650°C for 10 hours, and grind for another 2 hours to obtain the Au and Co co-doped holmium ferrite gas sensing material;

[0052] Among them, the added amount ratio of holmium nitrate, ferric nitrate, cobalt nitrate, chloroauric acid, citric acid and dilute nitric acid is 39.29g:14.51g:7.32g:4.58g:80g:80mL.

[0053] Example 3: Preparation of Au and Co co-doped holmium ferrite gas-sensitive material

[0054] (1) Mix holmium nitrate, ferric nitrate, cobalt nitrate and citric acid to obtain a mixture, then add the mixture into 9% by mass dilute nitric acid and stir for 6 hours to mix well to obtain a precursor solution;

[0055] (2) The precursor solution was heated in a water bath at 85°C, and stirred at a speed of 550 r / min for 2 h during the water bath heating process, and cooled to room temperature to obtain a solid; the solid was calcined at 1050°C for 3 h and then ground for 6 h to obtain a Co-doped holmium ferrite material;

[0056] (3) After mixing the Co-doped holmium ferrite material and chloroauric acid, grinding for 6 hours, calcining at 1050°C for 3 hours and grinding for another 6 hours, Au and Co co-doped holmium ferrite gas sensing material was obtained;

[0057] Among them, the added amount ratio of holmium nitrate, ferric nitrate, cobalt nitrate, chloroauric acid, citric acid and dilute nitric acid is 39.29g:21.77g:1.83g:0.92g:90g:90mL.

[0058] Example 4: Preparation of formaldehyde gas sensor

[0059] The Au and Co co-doped holmium ferrite gas-sensitive material prepared in Example 1, deionized water and pinene alcohol were mixed in an amount of 1 g: 3 mL: 1 mL to obtain a mixture, and the mixture was spin-coated on an Al2O3 substrate at a rotation speed of 600 rpm to form a gas-sensitive film with a thickness of 263 μm. The gas-sensitive film was then placed in air and aged at 220°C for 20 h to obtain a formaldehyde gas sensor.

[0060] Comparative Example 1: Preparation of holmium ferrite gas-sensitive material HoFeO3

[0061] (1) Mix holmium nitrate, ferric nitrate and citric acid to obtain a mixture, then add the mixture into 8.5% by mass dilute nitric acid and stir for 12 hours to mix well to obtain a precursor solution;

[0062] (2) The precursor solution was heated in a water bath at 80°C, and stirred at a speed of 500 r / min for 6 hours during the water bath heating process, and then cooled to room temperature to obtain a solid; the solid was calcined at 900°C for 8 hours and then ground for 3 hours to obtain a holmium ferrite material;

[0063] Among them, the added amount ratio of holmium nitrate, ferric nitrate, citric acid and dilute nitric acid is 39.29g:19.35g:60g:50mL.

[0064] Comparative Example 2: Preparation of Co-doped Holmium Ferrite Gas Sensing Material

[0065] (1) Mix holmium nitrate, ferric nitrate, cobalt nitrate and citric acid to obtain a mixture, then add the mixture into 8.5% by mass dilute nitric acid, stir for 12 hours to mix, and obtain a precursor solution;

[0066] (2) The precursor solution was heated in a water bath at 80°C, and stirred at a speed of 500 r / min for 6 hours in the water bath, and cooled to room temperature to obtain a solid; the solid was calcined at 900°C for 8 hours and then ground for 3 hours to obtain a Co-doped holmium ferrite gas-sensitive material;

[0067] Among them, the added amount ratio of holmium nitrate, ferric nitrate, chloroauric acid, citric acid and dilute nitric acid is 39.29g:19.35g:3.65g:60g:50mL.

[0068] Comparative Example 3: Preparation of Au-doped holmium ferrite gas-sensitive material

[0069] (1) Mix holmium nitrate, ferric nitrate and citric acid to obtain a mixture, then add the mixture into 8.5% by mass dilute nitric acid and stir for 12 hours to mix well to obtain a precursor solution;

[0070] (2) The precursor solution was heated in a water bath at 80°C, and stirred at a speed of 500 r / min for 6 hours during the water bath heating process, and then cooled to room temperature to obtain a solid; the solid was calcined at 900°C for 8 hours and then ground for 3 hours to obtain a holmium ferrite material;

[0071] (3) After mixing the holmium ferrite material and chloroauric acid, grind for 3 hours, calcine at 900°C for 8 hours, and grind for another 3 hours to obtain the Au-doped holmium ferrite gas-sensitive material;

[0072] Among them, the added amount ratio of holmium nitrate, ferric nitrate, cobalt nitrate, chloroauric acid, citric acid and dilute nitric acid is 39.29g:19.35g:2.29g:60g:50mL.

[0073] Test Example 1:

[0074] The Au and Co co-doped holmium ferrite gas-sensitive material prepared in Example 1 was characterized for its structure. Figure 1-Figure 3 shown.

[0075] Figure 1 is the XRD pattern of the formaldehyde gas-sensitive material obtained in Example 1. Figure 1 It can be seen that the crystallization peaks correspond to the (112), (111) and (200) phases of HoFeO3 (No.46-0115). Figure 2 The SEM images of the formaldehyde gas-sensitive material prepared in Example 1 at 60K and 100K magnifications are shown in FIG. Figure 2 It can be seen that the formaldehyde gas-sensitive material presents a typical nanoparticle structure, with a large specific surface area and porosity, and more reaction sites and transmission channels for gas molecules. Figure 3 From the XPS schematic diagram of gold and cobalt elements, it can be seen that Au and Co elements exist in the material, indicating that the two elements are doped into it.

[0076] Test Example 2:

[0077] The gas-sensitive materials prepared in Example 1 and Comparative Examples 1-3 were coated on the sensing film, and the gas-sensitive responses (Rg / Ra) of the gas-sensitive materials to 1 ppm of formaldehyde, nitrogen and other gases were tested respectively. The results are as follows: Figure 4-Figure 7 As shown. Among them, Ra is the resistance of the sensor in the air, and Rg is the resistance of the gas being measured. The experimental environment is: RH is 20%, and the ambient temperature is 20℃.

[0078] 1. Operating temperature

[0079] At different temperatures, the responses of various gas-sensitive materials to 1.0 ppm formaldehyde gas are as follows: Figure 4 As shown. Figure 4 It can be seen that the optimal working temperature of the gas-sensitive material prepared by the present invention is 140°C.

[0080] At a working temperature of 140°C, the response value of the gas-sensitive material prepared by the present invention to 1 ppm of formaldehyde gas is 5.96, the response value of the gas-sensitive material HoFeO3 prepared in comparative example 1 to 1 ppm of formaldehyde gas is 1.86, the response value of the gas-sensitive material prepared by doping the HoFeO3 material with only Co element in comparative example 2 to 1 ppm of formaldehyde gas is 2.53, and the response value of the gas-sensitive material prepared by surface loading and modifying the HoFeO3 material with only Au element in comparative example 3 to 1 ppm of formaldehyde gas is 4.22. It can be seen that the combined doping and modification of the HoFeO3 material with Au element and Co element has a synergistic effect in improving the response value of the gas-sensitive material to formaldehyde gas.

[0081] 2. Relative humidity

[0082] Under different relative humidity, the response of the Au and Co co-doped holmium ferrite gas-sensitive material prepared in Example 1 to 1.0 ppm formaldehyde gas is as follows: Figure 5 shown.

[0083] Depend on Figure 5 It can be seen that with the increase of relative humidity, the gas-sensing performance gradually decreases. When the relative humidity exceeds 40%, the gas-sensing performance drops sharply, but within 40%, the formaldehyde gas-sensing performance change rate of the material is within 5%, indicating that the material has extremely high gas-sensing relative humidity resistance.

[0084] 3. Selectivity

[0085] Example 1: The responses of Au and Co co-doped holmium ferrite gas-sensitive materials to different gases at 1.0 ppm are as follows: Figure 6 As shown by Figure 6 It can be seen that when exposed to multiple gases, the Au and Co co-doped holmium ferrite gas-sensitive material prepared by the present invention has significantly higher selectivity for 1 ppm formaldehyde gas than gases including CH5N, C2H7N, etc., which shows that the gas-sensitive material prepared by the present invention has good selectivity for formaldehyde gas.

[0086] 4. Long-term stability

[0087] Depend on Figure 7 It can be seen that the Au and Co co-doped holmium ferrite gas-sensitive material prepared by the present invention has long-term stability to 1 ppm formaldehyde gas. It can be seen that within one month, the response value change rate of the formaldehyde gas-sensitive material prepared by the present invention to 1 ppm formaldehyde gas is within 2%, indicating that the material has extremely high gas-sensitive long-term stability.

[0088] The above description is only the preferred embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.

Claims

1. An Au and Co co-doped holmium ferrite gas-sensitive material, characterized in that: The Au and Co co-doped holmium ferrite gas-sensitive material is prepared by the following method: (1) mixing holmium nitrate, ferric nitrate, cobalt nitrate and citric acid to obtain a mixture, then adding the mixture into dilute nitric acid and stirring to mix well to obtain a precursor solution; (2) heating the precursor solution in a water bath at 50-85°C and cooling it to obtain a solid; calcining the solid at 650-1050°C for 3-12h and then grinding it to obtain a Co-doped holmium ferrite material; (3) After mixing the Co-doped holmium ferrite material and chloroauric acid, the mixture is ground once, calcined at 650-1050°C for 3-12h, and then ground twice to obtain the Au and Co co-doped holmium ferrite gas sensing material; The added amount ratio of holmium nitrate, ferric nitrate, cobalt nitrate, chloroauric acid, citric acid and dilute nitric acid is (0.01-5) mol: (0.05-5) mol: (0.01-5) mol: (0.01-100) g: (20-100) g: (50-200) mL.

2. The Au and Co co-doped holmium ferrite gas-sensitive material according to claim 1, characterized in that: In step (1), the mass fraction of dilute nitric acid is 8-9%, and the stirring time is 6-12h.

3. The Au and Co co-doped holmium ferrite gas-sensitive material according to claim 1, characterized in that: In step (2), during the water bath heating process, the precursor solution is stirred at a stirring speed of 500-600 r / min and a stirring time of 2-8 h.

4. The Au and Co co-doped holmium ferrite gas-sensitive material according to claim 1, characterized in that: In step (2), the grinding time is 2-6 hours.

5. The Au and Co co-doped holmium ferrite gas-sensitive material according to claim 1, characterized in that: In step (3), the time for the first grinding and the second grinding is 2-6 hours.

6. Use of the Au and Co co-doped holmium ferrite gas-sensitive material according to any one of claims 1 to 5 in formaldehyde gas detection.

7. The use according to claim 6, characterized in that The concentration of the formaldehyde gas is 0.5-1.5 ppm.

8. Use of the Au and Co co-doped holmium ferrite gas-sensitive material according to any one of claims 1 to 5 in the preparation of a formaldehyde gas sensor.

9. The use according to claim 8, characterized in that The working temperature of the formaldehyde gas sensor is 80-200°C.

Citation Information

Patent Citations

  • Method for preparing transition state metal doped rare earth cobalt ferrite magnetostriction material by recycling waste lithium battery

    CN107331914A

  • Preparation method and application of perovskite type samarium ferrite

    CN116789181A